RE-ORIENTASI KEBIJAKAN EKSPOR SARANG BURUNG WALET INDONESIA KE CINA TAHUN (2012-2014) - ", Elvi; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study analyzed more about the policy change the indirect export to direct export by the Indonesian State to State China against bird's nest trade. Cultivation is a bird's nest industry special and very important to some communities in Indonesia. Bird's nest made of saliva bird that is considered beneficial to health. The bird's nest is usually used to make soup and most of the nests that produced in Indonesia is exported to China, especially Hong Kong.Indonesia has entered into a collaboration Mutual Recognition Agreement (MRA) with the Chinese government and followed up with a policy issued on Export Controls Swallow's Nest to the PRC. This study uses the theory of international trade as a theory relevant to the study. Based on the theory of international trade, the main motivation for doing international trade is getting gains from trade. The scope of this study which is from 2011-2013.Keywords: Bird Nest, direct export, trade, agreement.